2017
DOI: 10.1590/s1806-92902017000400011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium propionate and monensin on in vitro digestibility and gas production

Abstract: -An evaluation of the effects of monensin and calcium propionate on the in vitro kinetics of gas production, digestibility, carbon dioxide, and minor gas production on different days was performed using the ruminal fluid from eight Suffolk lamb donors, after receiving additives for 1, 10, and 20 days. Treatments consisted of a control ration of 40% grain; 30 mg/kg of monensin in a diet with 40% grain; 10 g/kg calcium propionate in a diet with 30% grain; and the combination of both additives in a diet with 30% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…When CaPr is supplemented alone, it undergoes hydrolysis within the acidic pH of the rumen, resulting in the formation of Ca 2+ and propionic acid [7]. This process yields several effects at the rumen level, including (1) alteration of the volatile fatty acid (VFA) pattern [5]; (2) reduction in methane production; (3) improved digestibility of the DM; (4) enhanced fermentation efficiency [4]; and (5) improved responsiveness of insulin in glucose metabolism [6], which plays a role in both fat deposition and muscle growth. As a cumulative outcome of these mechanisms, there is a promotion of energy status achieved through the heightened synthesis of glucose via gluconeogenesis [7].…”
Section: Productive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…When CaPr is supplemented alone, it undergoes hydrolysis within the acidic pH of the rumen, resulting in the formation of Ca 2+ and propionic acid [7]. This process yields several effects at the rumen level, including (1) alteration of the volatile fatty acid (VFA) pattern [5]; (2) reduction in methane production; (3) improved digestibility of the DM; (4) enhanced fermentation efficiency [4]; and (5) improved responsiveness of insulin in glucose metabolism [6], which plays a role in both fat deposition and muscle growth. As a cumulative outcome of these mechanisms, there is a promotion of energy status achieved through the heightened synthesis of glucose via gluconeogenesis [7].…”
Section: Productive Performancementioning
confidence: 99%
“…It has been observed that the gluconeogenic precursor calcium propionate (CaPr) alters energy metabolism in two ways when supplemented in ruminant diets: firstly, by altering rumen fermentation through improvements in ruminal dry matter (DM) digestibility, thereby increasing the proportion of ruminal propionate, and decreasing methane production [4,5]. Another way is by improving insulin's action on glucose metabolism [6], thereby promoting an increase in energy status through enhanced glucose synthesis via gluconeogenesis in the liver [7].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to an acetate:propionate ratio decline [3,[84][85][86], which in turn favours the recovery of energy used by the animal [79]. Additionally, SM reduces the formation of methane and lactic acid produced by other microorganisms [87,88].…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…(29). En otro estudio in vitro con 10% de Pr-Ca, el volumen de gas aumentó el cual fue atribuido a los efectos sobre pH y a la presión osmótica (8). En una evaluación in vivo con toros recibieron 20 g/d de Pr-Ca, no afectaron la fermentación ni la población microbiana (30), pero la dosis fue muy baja.…”
Section: Discussionunclassified
“…El propionato de calcio (Pr-Ca) como una fuente de alimentación no convencional ha sido utilizado en corderos para reducir el uso de granos, incrementando el propionato ruminal (7). Su potencial para reducir el metano se explica porque durante su disociación captura el ion de hidrógeno reduciendo su disponibilidad para formar metano (8). Las emisiones de GEI pueden reducirse si se mejora la digestibilidad, lo cual se alcanza cubriendo las necesidades nutricionales, particularmente en rumiantes alimentados con dietas con forrajes de baja calidad (9).…”
Section: Introductionunclassified